Validasi Kuesioner Kepatuhan Protokol Kesehatan COVID-19: Analisa Eksploratori Faktor dan Nilai Titik Potong - Pinta Pudiyanti Siregar; Des Suryani (JURNAL IMPLEMENTA HUSADA, 2021)
The COVID-19 pandemic has forced many countries in the world to enforce strict health protocols. The public is expected to comply with the protocol in an effort to reduce the number of morbidity and even death due to COVID-19 which is increasing. We need a measuring tool that can be trusted both validity and reliability so that it can determine the extent to which the community adheres to health protocols. From 88 respondents, it was found that the value of the questions on this questionnaire had a good measuring value. This questionnaire is an alternative to measure community compliance in carrying out health protocols during the COVID-19 pandemic. Further research is needed to assess this questionnaire so that it has more appropriate validity and reliability in assessing community compliance.